2018
DOI: 10.3389/fimmu.2018.01201
|View full text |Cite
|
Sign up to set email alerts
|

CD8+HLADR+ Regulatory T Cells Change With Aging: They Increase in Number, but Lose Checkpoint Inhibitory Molecules and Suppressive Function

Abstract: CD4+ regulatory T cells have been intensively studied during aging, but little is still known about age-related changes of other regulatory T cell subsets. It was, therefore, the goal of the present study to analyze CD8+human leukocyte antigen–antigen D related (HLADR)+ T cells in old age, a cell population reported to have suppressive activity and to be connected to specific genetic variants. We demonstrate a strong increase in the number of CD8+HLADR+ T cells with age in a cohort of female Sardinians as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…We chose several classical phenotype markers of lymphocytes including CD28 (naive marker), CD45RA (naive marker), HLA-DR (activated marker) and CD45RO (memory marker) to reflect host immunity. These phenotype markers are correlated with lymphocyte function and are known to play an important role in many diseases such as infection, tumor, and autoimmune disease [24][25][26][27]. As expected, our data demonstrated that the expression of CD28 on T cells gradually decreased with increasing age and was negatively correlated with their function.…”
Section: Discussionsupporting
confidence: 85%
“…We chose several classical phenotype markers of lymphocytes including CD28 (naive marker), CD45RA (naive marker), HLA-DR (activated marker) and CD45RO (memory marker) to reflect host immunity. These phenotype markers are correlated with lymphocyte function and are known to play an important role in many diseases such as infection, tumor, and autoimmune disease [24][25][26][27]. As expected, our data demonstrated that the expression of CD28 on T cells gradually decreased with increasing age and was negatively correlated with their function.…”
Section: Discussionsupporting
confidence: 85%
“…CD8 + HLA-DR + cells suppress in a cell-to cell contact dependent manner, which involves CTLA-4 ( 47 ). Within the CD8 + HLA-DR + Treg cells the CD28 + subpopulation shows higher suppressive capacity compared to their CD28 - counterparts and also expresses higher levels of the checkpoint inhibitory molecules CTLA-4, TIM-3, PD-1 and LAG-3 ( 61 ). Similarities have been found between CD8 + HLA-DR + and CD4 + Foxp3 + Treg with regards to the expression of TIGIT, the chemokine receptors CCR4 and CCR5, the low expression of IL-7R (CD127) and a memory and effector-like phenotype.…”
Section: Subsets Of Regulatory T Cellsmentioning
confidence: 99%
“…Despite the fact that CD8 + HLA-DR + Treg accumulate with age, the expression of CD28 in these cells remains unchanged. CD8 + HLA-DR + Treg cells lose suppressive activity and decrease the production of checkpoint inhibitory molecules in aged individuals ( 61 ).…”
Section: Treg Homeostasis and Function In Agingmentioning
confidence: 99%
“…Despite the lack of independent validation, our ability to reproduce previously published healthy age/gender effects on blood immune cells within an identical HD cohort strengthens the probability that CSF data is, likewise, reproducible in future studies. These reproduced age changes in blood include declines in proportion of plDCs with age (42), increases in CD56+ NK cells (43)(44)(45)(46) with age, positive correlation of HLA-DR+ CD8+ T cells (47,48) and HLA-DR+ CD4+ T cells (47) with age, increases in CD4+ T cell/CD3+ T cell ratio with age (49), and increases in proportion of CD3+ T cells (50,51) and proportion of CD4+ T cells with age (51). Reproduced gender differences in blood include a higher presence of B cells in females (52), higher CD4/CD8 ratio in females (53,54), higher proportion of CD8+ T cells in males (54), and higher presence of HLA-DR+ CD4+ T cells and HLA-DR+ CD8+ T cells in males (55).…”
Section: Discussionmentioning
confidence: 99%